Assessing structural damage progression in psoriatic arthritis and its role as an outcome in research - van der Heijde, Désirée (Arthritis Res Ther, 2020)
Psoriatic arthritis (PsA) is an immune-mediated, clinically heterogeneous disease characterized by arthritis, enthesitis, dactylitis, spondylitis, and psoriasis of the skin and nails. Persistent articular inflammation in patients with PsA can lead to structural damage, which can result in reduced physical function and quality of life. Structural damage can occur rapidly, and irreversible joint damage may be observed if patients are not treated promptly and appropriately. Therefore, evaluating therapeutic agents for their ability to inhibit structural progression has become increasingly important, with radiographic progression becoming a key efficacy outcome in clinical trials in PsA. Here, we review how structural damage and progression are assessed in clinical trials and the use of radiographic progression as a study outcome. We also discuss possible limitations in the current assessment of radiographic progression as well as areas of research that may improve the assessment of structural damage in clinical trials of PsA.